ANALISIS PENGARUH DISIPLIN KERJA, STRESS KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI (Studi pada Pegawai Dinas Perkebunan Provinsi Jawa Tengah) - Luki Haryuni, 10.05.51.0146 (Students Journal of Economic and Management, 2014)
Empirical phenomena found in the research shows that the realization of annual performance Plantation Office of Central Java Province has not been able to meet the targets set by the institution which is an indication that the performance of employees in the Department of Horticulture of Central Java Province is low. From the above it can be concluded that the issues raised in this study is: "How to improve performance in Department of Horticulture of Central Java province?". Problems developed in this study answered through testing variables work discipline, job stress, and work motivation on employee performance. The data obtained through the interviews necessary to 117 employees of the Department of Horticulture of Central Java Province by using the questionnaire. The data were then analyzed using multiple regression test. Regression testing results show that the discipline of work proved significant positive effect on the performance of employees in the Department of Horticulture of Central Java province, job stress proved significant negative effect on the performance of employees in the Department of Horticulture of Central Java Province, work motivation proved significant positive effect on the performance of employees in the Department of Horticulture Central Java Province, as well as the discipline of work, job stress, and motivation to work together proved to have a significant effect on the performance of employees in the Department of Horticulture of Central Java Province.Keywords: work discipline, job stress, work motivation, performance